2008
DOI: 10.1007/s12182-008-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of mixed-source crude oils and its significance for understanding oil accumulation in subtle pools in the Dongying Depression, Bohai Bay Basin

Abstract: Conventional geochemical approaches were utilized in the quantitative prediction of the proportions of mixed-source crude oils derived from the Es 3 and Es 4 members of the Paleogene Shahejie Formation. The mixed-source oils are accumulated in the middle interval of the Es 3 member (Es 3 M ) in the Niuzhuang Sag, which is one of the sags where subtle traps are primarily of lenticular basin-floor turbidite sands within mudstones mostly developed in the Dongying Depression, Bohai Bay Basin. The result showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Although there is a lack of carbon isotope data lower than n-C 15 in the study samples, the curve trend shows that there is a high possibility of a max carbon peak of n-C 15 . There is a max peak carbon of n-C 32 (Figure 8), is basically consistent with previous research results [36], indicating that the crude oil samples in the study area are more likely to be derived from the Es 3 source rock.…”
Section: Sedimentary Environment Comparisonsupporting
confidence: 91%
See 2 more Smart Citations
“…Although there is a lack of carbon isotope data lower than n-C 15 in the study samples, the curve trend shows that there is a high possibility of a max carbon peak of n-C 15 . There is a max peak carbon of n-C 32 (Figure 8), is basically consistent with previous research results [36], indicating that the crude oil samples in the study area are more likely to be derived from the Es 3 source rock.…”
Section: Sedimentary Environment Comparisonsupporting
confidence: 91%
“…In Figure 8, it can be seen that there is a certain similarity between three crude oils, indicating a high correlation between the crude oils, and the sedimentary environment also has a certain similarity. The Es 3 formation in the study area is brackish or a freshwater delta facies deposition, which is highly consistent [36] with the carbon isotope values. In addition, previous studies in neighboring areas found that the crude oil generated from the Es 3 source rock has relatively heavy carbon isotopes and shows a double-peak curve with the max carbon peaks of n-C 15 and n-C 32 [37].…”
Section: Sedimentary Environment Comparisonsupporting
confidence: 86%
See 1 more Smart Citation
“…The second episode was relatively late, allowing oil to accumulate in a variety of traps formed prior to and during source rock maturation. Many reservoirs are found in the Es U 3 and Ed members [27].…”
Section: Petroleum Systemsmentioning
confidence: 99%
“…A transfer zone is a kinematic and dynamic transition zone between major faults, and the zone transfers strain by transmitting the displacements of major faults or secondary faults [27,29]. The fault expansion index and throw can be used to characterize the strain transition.…”
Section: Kinematic and Dynamic Characteristics Of The Faultsmentioning
confidence: 99%